2012
DOI: 10.1371/journal.pone.0047748
|View full text |Cite
|
Sign up to set email alerts
|

Soluble IL-2Rα (sCD25) Exacerbates Autoimmunity and Enhances the Development of Th17 Responses in Mice

Abstract: A strong association exists between mutations at the IL2 receptor alpha chain (CD25) gene locus and susceptibility to a number of T cell driven autoimmune diseases. Interestingly, the presence of certain CD25 susceptibility alleles has been correlated with significantly increased levels of the soluble form of CD25 (sCD25) in the serum of patients. However, the functional consequences, if any, of this observation are unknown. We have demonstrated that elevated levels of sCD25 in vivo resulted in exacerbated exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 34 publications
4
49
0
2
Order By: Relevance
“…sCD25 suppresses IL-2-induced surface CD25 expression and T cell responses in vitro [30,31,[53][54][55]. Russell et al [56] reported that sCD25 can exacerbate experimental autoimmune encephalitis by acting as a decoy receptor that sequesters IL-2, eventually altering the balance between Th1/Th17 and Tregs. A different mechanism might explain the capacity of sCD25 to subvert the immunostimulatory effects of CTLA-4 blockade.…”
Section: -Test) (F)mentioning
confidence: 99%
“…sCD25 suppresses IL-2-induced surface CD25 expression and T cell responses in vitro [30,31,[53][54][55]. Russell et al [56] reported that sCD25 can exacerbate experimental autoimmune encephalitis by acting as a decoy receptor that sequesters IL-2, eventually altering the balance between Th1/Th17 and Tregs. A different mechanism might explain the capacity of sCD25 to subvert the immunostimulatory effects of CTLA-4 blockade.…”
Section: -Test) (F)mentioning
confidence: 99%
“…1C) showing that the mice treated with anatabine displayed significantly milder disease symptoms than the placebo group. We euthanatized the mice at day 16 following the immunization for pathological and biochemical evaluations because it has been shown that the peak of EAE disease severity is generally reached around day 16 in similar MOG immunization models [12], [13]. We first assessed the titer of circulating antibodies reacting against murine MOG 35–55 in the serum of control non-immunized mice, EAE placebo and EAE anatabine treated mice.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, we observed extremely high sCD25 levels in Prf1 2/2 mice sera compared with wild-type mice on day 10 after infection (Fig 6, A). This not only recapitulates a key component of FHL, but because sCD25 might have the capacity to compete with CD25 for IL-2 binding, 24 it adds an additional mechanism by which Wild-type and Prf1 2/2 mice were infected with LCMV-Armstrong and assessed at days 0, 5, and 10 for CD8 1 T-cell activation in the lymph nodes. A, CD8 1 T-cell subpopulations were characterized as CD8 1 CD62L 1 CD44 2 naive cells, CD8 1 CD62L 1 CD44 1 central memory T cells (TCM), and CD8 1 CD62L 2 CD44 1 effector memory T cells (TEM) by means of flow cytometry.…”
Section: Lcmv Infection In Perforin-deficient Mice Disrupts Il-2 Consmentioning
confidence: 89%